Satisfaction evaluation for ACLS training - Stirparo, Giuseppe; Gambolò, Luca; Bellini, Lorenzo; Medioli, Filippo; Bertuol, Maria; Guasconi, Massimo; Sulla, Francesco; Artioli, Giovanna; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2022)
Abstract.Background and aim: simulation became gradually pivotal in training of health professionals: indeed, it showed an improvement in practical skill of the trainees compared to theoretical lectures. Among others, ACLS (advance cardiovascular life support) courses are now one of the standard learning practices most spread around the world.The primary aim of this study is to evaluate both the level of satisfaction and the clinical thinking that the trainees perceived during an ACLS course. This was performed via the SSE validated scale (Satisfaction with simulation experience scale). The secondary aim was to evaluate if demographics affect the aforementioned perceived satisfaction.Methods: a SSE questionnaire was distributed after the ACLS section of practical scenarios, just before the end of the course and of the practical test.Results: 72 questionnaires have been collected. The sample was constituted by 68.1% of females, 44,4% by nurses without a master’s degree, and 52,8% personnel that works outside of a critical care setting. QTOT Median score was 89 (IQR=86-90), DTOT Median’s 45 (IQR= 44.25-45), RTOT Median’s 25 (IQR=22-25), LTOT Median was 20 (IQR=19-20). Conclusions: The ACLS course attains a high grade of satisfaction on all of the three aspects evaluated by the questionnaire. The perception was not influenced by the demographics.